Credit market development and agricultural production in selected African countries: Climate change perspective - Zewdie Habte Shikur (REGION, 2023)
This study aimed to examine the long and short-run relationships between credit market development and agricultural production using the Autoregressive Distributed Lags (ARDL) Bounds test for cointegration, as well as the direction of causality by using the Granger causality test. The results of the ARDL Bounds test revealed that institutional credit development had a significant long-run effect on agricultural production in all countries under examination, except for Tunisia; that is: Benin, Kenya, and Nigeria. In the short run, credit market development had a significant and positive effect on agricultural production in Nigeria. By contrast, the effect of credit market development on agricultural production was negative in the short-run in Benin, Kenya, and Tunisia. The result of granger causality test revealed the existence of significant bi-directional causal links between institutional credit development and agricultural production in Benin, Kenya and Nigeria, no significant interdependence was found between the two variables in Tunisia. Capital formation had a significant and positive effect on agricultural production in the long-run and short-run in all countries. Climate change was negatively associated with agricultural production in all countries except for Nigeria. The exchange rates and real interest rates had a negative effect on agricultural production in the long-run and short-run in all countries.
Keywords: F33; Q11; Q14; 330; agricultural production; credit market development; real interest rate; agricultural loan supply; climate change